The Effect of Adoption of International Public Sector Accounting Standards on Quality of Financial Reports in Public Sector in Kenya - Opanyi, Robert O. (European Scientific Journal, ESJ, 2016)
Quality financial reports plays significant role in accountability of government to their citizens and how it meets its financial management responsibilities. The introduction of IPSAS formed an important part of public sector reforms and followed a global trend in government accounting in response to calls for greater government financial accountability and transparency which is a fundamental principles of democracy. This study focused on effect of adoption of IPSAS on quality of financial reports in meeting the criteria for decision usefulness. The design of this study was the descriptive survey design while the target population was the 19 ministries of the national government in Kenya. Data was collected using secondary means and was analysed using descriptive statistics and t-test for differences. The study indicated enhancement in the quality of characteristics of comparability, relevance, timeliness and faithful representation by adoption of IPSAS while the quality of characteristics of understandability declined. The study also showed no significant difference in items pertaining to transparency and accountability indicating that the goal for government reforms in achieving greater transparency and accountability may not be fully achieved. The study also revealed that adoption of IPSAS is adjudged to have moderate effect on quality of financial reports in public sector in Kenya using a 5 point likert scale. The study concluded that there exist statistically significant difference between old accounting standard-based financial reports and IPSAS-based financial reports in meeting the criteria for decision usefulness as revealed by paired-sample t-test.